Laryngeal Fracture after Blunt Cervical Trauma in Motorcycle Accident and Its Management - Nuno Ribeiro-Costa; Pedro Carneiro Sousa; Diogo Abreu Pereira; Paula Azevedo; Delfim Duarte (Case Reports in Otolaryngology)
Laryngeal fracture is a rare traumatic injury, potentially fatal, with an estimated incidence of 1 in 30,000 patients admitted to severe trauma centers. Because of the rarity of this injury, physician may be not aware of its existence, leading to a late diagnosis of this entity. We report a case of a 59-year-old woman admitted to the emergency room after a motorcycle accident with cervical trauma. The patient presented with dysphonia, hemoptysis, cervical subcutaneous emphysema, and increasing respiratory distress that led to the intubation of the patient. CT-scan demonstrated displaced fracture of the cricoid and thyroid cartilage. The patient was submitted to tracheostomy and the fracture was surgically repaired. Tracheostomy was removed in third postoperative month. The patient presented a good recovery, reporting only hoarseness but without swallowing or breathing problems at 6-month follow-up.